The Effectiveness of Schema Therapy on Obsessive-Compulsive Disorder in Individuals with Borderline Personality Disorder - Modaresi , Mona (Health Nexus, 2025)
Borderline personality disorder, a severe and pervasive mental health condition, has attracted the interest of many researchers. Therefore, the present study aimed to examine the effectiveness of schema therapy on obsessive-compulsive disorder in individuals with borderline personality disorder. This study employed a quasi-experimental design with a pretest-posttest control group structure. The statistical population included all married women diagnosed with borderline personality disorder who visited the Family Green Psychological Services Center in Semnan in 2024. From this population, 30 individuals were selected using purposive sampling based on inclusion and exclusion criteria and were randomly assigned to either the experimental or control group (15 participants per group). The research instrument was the Maudsley Obsessive-Compulsive Inventory (MOCL). The schema therapy sessions were conducted based on the schema therapy protocol developed by Young et al. (2003; translated by Hamidpour, 2007). Data analysis was performed using SPSS-24 software and multivariate analysis of covariance (MANCOVA) while ensuring statistical assumptions were met. The results indicated that after controlling for the pretest effect, the difference in pretest-posttest scores in the experimental group for obsessive-compulsive disorder was statistically significant. Additionally, the posttest mean scores for obsessive-compulsive disorder in the experimental group were significantly lower than those in the control group (p < .001). Based on the study findings, schema therapy has a significant impact on the research variables. To enhance the external validity of the findings, further studies in this area are recommended.